Expatriate management : transatlantic dialogues - Bader, Benjamin; Schuster, Tassilo; Bader, Anna Katharina (Palgrave Macmillan, 2017)
This book provides state-of-the art research on expatriate management from a European perspective. Considering issues related to the different phases of expatriation and comprehensive contemporary topics of expatriate management, the chapters present a long overdue holistic approach to the field. Rather than just publishing a counterweight to the predominant North American literature, Expatriate Management includes critical analyses of each chapter written by a number of renowned North American scholars to review and contribute to the trans-Atlantic dialogue.- Resumé vydavatel
Keywords: zahraniční pracovní síly; personální management; politika zaměstnanosti; nadnárodní společnosti; foreign workers; personnel management; manpower policy; international business enterprises; elektronické knihy; sborníky; electronic books; papers of several authors